Spermiogenesis in the caryophyllidean cestode Khawia armeniaca (Cholodkovski, 1915) - Brunanská, Magdaléna; Poddubnaya, Larisa G (Parasitology research, 2006)
Spermiogenesis of the monozoic cestode Khawia armeniaca (Cholodkovski, 1915), a parasite of Capoeta capoeta sevangi (De Filippi, 1865) (Pisces: Cyprinidae), has been investigated by means of transmission electron microscopy for the first time. The present results show that the type of spermiogenesis in K. armeniaca shares the main features described previously in the pseudophyllideans and/or spathebothriideans: apical dense material in the zone of differentiation in the early stages of spermiogenesis, rotation of flagellum and flagellar bud, proximodistal fusion, and penetration of the nucleus into the spermatid body after the fusion of the free flagellum with the MCP has started. However, only one axoneme and a simple intercentriolar body represent presumably more evolved characters, typical for "higher" tapeworms. Ultrastructural data of spermiogenesis in K. armeniaca may support the hypothesis that the Caryophyllidea are secondarily derived from an ancestor closely allied with the Pseudophyllidea.
Keywords: Cestoda; spermatogeneze; spermie; Spermatozoa; Male; Animals; Spermatogenesis; mužské pohlaví; Microscopy, Electron, Transmission; Testis; zvířata; transmisní elektronová mikroskopie; testis